2D Assembly of Atomically Oriented Gold Nanodisks Leads to Tunable Plasmonic Resonance - Maiti, Santanu; Sanyal, Milan K.; Chumakov, Andrei; Khan, Ali Hossain; Maji, Subrata; Satpati, Biswarup; Mukhopadhyay, Mrinmay K.; Acharya, Somobrata (Journal of Physical Chemistry C, 2023)
Nanocrystals (NCs) are extensively used to create self-assembled nanostructures; however, little has been achieved on the assembly of NCs with an anisotropic shape. A key challenge with the anisotropic NCs is assembling them into positional order with preferential atomic crystallographic orientations. Here, we use the air-liquid interface to prepare two-dimensional (2D) assemblies of crystalline gold nanodisks (AuNDs) with preferentially oriented atomic lattices and report on the in situ structural and optical properties of the nanostructures. The structure of 2D assemblies driven by in-plane surface pressure was monitored using grazing incidence small-angle X-ray scattering (GISAXS) and grazing incidence X-ray diffraction (GIXD), and optical properties were monitored using UV-vis spectroscopy. We observe that the preferentially oriented atomic lattice of the NDs leads to the formation of 2D hexagonal superlattices, exhibiting a continuous blue shift of the plasmonic band with increasing surface pressure. We quantify the packing by X-ray scattering to understand the plasmonic properties induced by the surface pressure. This controlled process to tune the plasmon resonance property paves a novel way to establish the essential correlation between the structure and properties of anisotropic NCs and opens door to the rational design of programmable NC networks.
CRIS-Team WoS Importer:2023-05-05